THE ‘EAST/WEST’ DIVIDE AND EUROPE’S RELOCATION SYSTEM FOR ASYLUM SEEKERS - Bejan, Raluca (Ревија за социјална политика/Journal of Social Policy, 2016)
For the most part of 2015, Europe was confronted with an unprecedented inflow of refugees and asylum seekers.The numbers of irregular migrants arriving on the shores of Italy, Greece and later, Hungary, have pushed these states into an emergency situation. It is why the European Commission invoked a provisional relocation mechanism to transfer displaced persons in need of international protection to other European Union (EU) member states. TheCommission developed a distribution key, based on the weighted indicators of GDP (40%), size of the population(40%), unemployment rate (10%) and past number of asylum seekers applications (10%), to proportionally share responsibility for settling the numbers of refugees and asylum seekers already present on European soil. The plan was vehemently opposed by many Eastern Bloc countries, which voted against the suggested mandatory quotas. Explanations were quickly framed around the culturally backward concepts of these nations: xenophobia, racism, their far-right political orientation and the internalized conditioning of being branded solely as emigration versus immigration states. Less attention was paid, however, to understanding such political reaction(s) as contextually grounded within an unequal and differential positioning that post socialist countries occupy within the EU. This paper draws from the field of taxation policy to critically examine proposed EU relocation quotas, in an effort to contextually understand the Eastern bloc reaction to the refugee crisis. It uses the notions of horizontal equity and vertical equity to demonstrate how the current relocation scheme is progressive in application, yet fat in impact, since it proportionally equalizes the share of responsibility, without progressively adjusting it to match states’ capabilities for relocation (i.e. it does not account for the political and cultural unequal position of the Eastern Bloc states, as an a priori structured and structuring condition within the Union).
Keywords: Europe’s refugees crisis; EU relocation system; EU distribution key; Horizontal equity; Eastern Bloc; East/West divide; Mandatory quotas